UPAYA GURU PJOK DALAM PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 TERHADAP HASIL BELAJAR SISWA - Fikri Fauzi, - (2022)
This study aims to identify and describe the efforts made by PJOK teachers in online learning during the COVID-19 pandemic at SMA Negeri Bandung City, East Region. The method used in this study is descriptive analysis with instruments in the form of a google form questionnaire and grades of report cards for the even semester of 2022. The population in this study were PJOK teachers at SMAN Bandung City, East Region. The sampling technique used purposive sampling with the number of teachers in the corner as many as 12 people. The results of the study show that the efforts of PJOK teachers in carrying out online learning seen from the aspects carried out are said to be quite good, as evidenced by the average achievement of student learning outcomes that exceed the KKM value. Learning outcomes are high because everything is easily accessible online. This study proves that the efforts made by PJOK teachers on student learning outcomes are said to be good and can be a reference for others.